First among equals. Vol. 1 [videorecording (DVD)] - Gorrie, John; Mills, Brian; Harding, Sarah; Child, Jeremy; Faulkner, James, 1948-; Robb, David, 1947-; Wilkinson, Tom, 1948-; Archer, Jeffrey, 1940- (Distributed by Acorn Media, 2008)
Beginning in 1964, this television drama follows the careers of four members of Parliament from their backbench days through 20-plus years of alliances and betrayals, triumphs and reversals. Each man aims to become prime minister-- but only one will succeed.